2012
DOI: 10.1039/c2jm31709e
|View full text |Cite
|
Sign up to set email alerts
|

Amines as dual function ligands in the two-phase synthesis of stable AuxCu(1−x) binary nanoalloys

Abstract: The synthesis of Au x Cu (1Àx) nanoalloys (NAs) by a two-phase method employing amines acting simultaneously as coordinating ligands, phase transfer agents as well as nanoparticle (NP) stabilisers, is presented. The value of x was varied between 0 and 1 and dodecylamine (DDA) and hexadecylamine (HDA) were used as ligands. The nanoparticles were characterised by elemental analysis, UV-vis and IR spectroscopies, X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), scanning TEM (STEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Selected area electron diffraction (SAED) measurements confirmed the crystalline nature of Au and LAGP particles. The selected patterns show interplanar spacings of 2.36 Å for Au-(111) (Dilshad et al, 2012) and 3 S4A,B). Very few cavities are observed between the grains (except the ones created by the ion beam), confirming the good sintering of the particles.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Selected area electron diffraction (SAED) measurements confirmed the crystalline nature of Au and LAGP particles. The selected patterns show interplanar spacings of 2.36 Å for Au-(111) (Dilshad et al, 2012) and 3 S4A,B). Very few cavities are observed between the grains (except the ones created by the ion beam), confirming the good sintering of the particles.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…When exposed to a hydrogen atmosphere, amido complexes are expected to release the corresponding amine in the course of the reaction, a class of ligands oen used in NPs synthesis and stabilization. [10][11][12][13] Contrarily coordination of amido ligands at the surface of NPs was only seldom discussed. 36 Here, DFT calculations showed that: (1) adsorption of the diphenylamido ligand is signicantly more favourable on the iron surface than that of DPA, (2) adsorption of the bis(trimethylsilyl) amido ligand is only slightly more favoured than that of HMDS and (3) adsorption energies of all amines are comparable.…”
Section: Stabilization Of Iron Npsmentioning
confidence: 99%
“…When exposed to an hydrogen atmosphere, amido complexes are expected to release the corresponding amine in the course of the reaction, a type of ligand oen used to control the stability and morphology of NPs in colloidal solutions. [10][11][12][13] [Fe(N(SiMe 3 ) 2 ) 2 ] 2 has been reported by our group and others to afford iron NPs of controlled size and shape, and deprived of any surface oxidation, affording systems particularly adapted to investigate surface magnetism at the nanoscale. [14][15][16][17][18][19] Surface effects are best observed on NPs which display a high enough proportion of surface atoms, namely those having a size below 3 nm.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that with hexadecylamine and PVP, complexes of Au 3+ were formed in solution. Nitrogen ligand coordination compounds of Au 3+ have not been studied extensively [48]. Nagel and Beck [49] have reported that the reaction of AuCl 4 with n-butylamine led to the formation of the imine ClAuNH=R, by a ligand displacement reaction.…”
Section: Resultsmentioning
confidence: 99%